The Correlations between Students’ Reading Habits and Pronunciation Ability at the Eleventh Grade of SMA Negeri 20 Pangkep - ita Purnama Sari; Syarifuddin Dollah; Amra Ariyani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This research aimed to determine the student’s reading habits and pronunciation ability and the relationship between their reading habits and pronunciation ability. A correlational research design was used in the research. Twenty-eight students from the eleventh grade at SMA Negeri 20 Pangkep were chosen using the cluster random sampling technique as the sample group for this research. This research used a questionnaire to learn about the reading habits of the students and a pronunciation test to assess their pronunciation abilities. The findings of this research show that: (1) the eleventh-grade students at SMA Negeri 20 Pangkep had often category reading habits (Repeat reading English text twice or more). (2) The students' pronunciation abilities are good-categorized, and (3) the correlation between students’ reading habits and pronunciation ability was positive because r calculation = 0.924 was higher than the value of r table = 0.329, which means that the H0 of this research was rejected and H1 was accepted. Therefore, it can be concluded that there was a significant correlation between the students’ reading habits and pronunciation ability in the eleventh grade of SMA Negeri 20 Pangkep.